Aspek Hukum Perlindungan Kepada Para Investor Perusahaan Financial Technology Apabila Debitornya Tidak Melakukan Pembayaran dan Akibat Hukumnya - Syafa Karimah; Margo Hadi Putra (Jurnal Ilmiah Wahana Pendidikan, 2021)
the author is interested in conducting research that aims to determine the legal consequences if the debtor does not make loan payments to financial technology companies; to determine the position of the Investor in a financial technology company if the debtor does not make loan payments; to find out the legal protection of investors in financial technology companies if the debtor does not make payments. The approach method used in this research is a normative juridical approach. That is the study of theories, concepts, legal principles and laws and regulations related to financial technology. , cancellation of agreement, transfer of risk, paying court fees. The position of the Investor in a financial technology company if the Debtor does not make loan payments is as the Creditor. Investors' legal protection in financial technology companies if the debtor does not make loan payments can be found in the arguments for the lawsuit for default, which refer to Article 1239 in conjunction with Article 1243 and Article 1267 of the Civil Code.